Quality and the English language question: Is there really an issue in Australian universities? - Briguglio, Carmela (Routledge Taylor & Francis Group, 2011)
English language proficiency and how it can be improved have been keenly debated issues in Australian universities. The debate has become more intense in the context of the marketing of international education and Australia’s increasing share of international students. One reaction has been to raise the minimum English language levels for university entrance but this solution provides only a temporary panacea that hides important related issues. Today’s university students are operating in a world where intercultural interactions are the norm and people who can comfortably negotiate cultural and linguistic differences are required. This article argues that the extensive cultural and linguistic diversity of the student body on many university campuses should not be feared as leading to a lowering of standards in English. Rather, such diversity needs to be harnessed to develop the intercultural communication skills required in the global workplace. This can be achieved if universities desist from viewing the English language question through a deficit lens and, instead, place English language development and support issues at the centre of internationalisation initiatives.